Prevalence of osteoporosis in patients awaiting unicompartmental knee arthroplasty: a cross-sectional study - Zhuang, Zhikun; Huang, Changyu; Chen, Xianyi; Wei, Qiushi; Guo, Jinhua; Xu, Zhiqing; Wu, Rongkai; Wu, Zhaoke; Xu, Fudong (Frontiers in Endocrinology, 2023)
Objectives: Osteoporosis may contribute to failure of unicompartmental knee arthroplasty (UKA), yet the prevalence of osteoporosis in the population awaiting UKA has not been adequately studied. The objectives of this study were to report the prevalence of osteoporosis in people awaiting UKA and the rate of anti-osteoporosis treatment, and to explore factors associated with osteoporosis prevalence in people awaiting UKA. Methods: Participants awaiting UKA from January 2019 to May 2023 were consecutively enrolled. Participants ' age, gender, BMI, knee K-L score, VAS score, history of previous DXA testing, history of anti-osteoporosis treatment, and possible underlying risk factors were recorded. All participants were given a dual-energy x-ray absorptiometry (DXA) test after the visit. The diagnosis of osteoporosis was made according to the World Health Organization criteria. Compare the prevalence of osteoporosis between people waiting for UKA and the general population. Risk factors associated with osteoporosis were analyzed using multiple linear regression and binary logistic regression models. Results: A total of 340 participants were included in the study, 259 in female and 81 in male, with a mean age of 63.53 years (range: 41-84 years), and all participants completed UKA and had DXA prior to UKA. The prevalence of osteoporosis was 40.88% (44.79% in female and 28.40% in male). The prevalence of osteoporosis was higher in female than in male (p<0.001). The prevalence of osteoporosis in the population waiting for UKA was significantly higher than that in the general population (p < 0.001). DXA testing was performed in 12.06% within 1 year prior to the visit. The percentage of those who had received anti-osteoporosis treatment was 20.59% (20.86% in osteoporosis, 22.39% in Osteopenia and 16.42% in normal bone mass). The correlation between age, gender, body mass index, visual analogue scale score and osteoporosis was statistically significant. Conclusions: Osteoporosis is common in people waiting for UKA, but screening and treatment rates are low. Female patients of advanced age and low weight combined with significant pain should be considered for osteoporosis screening and appropriate treatment before UKA.